An inductive-capacitive-circuit-based micro-electromechanical system wireless capacitive pressure sensor for avionic applications: Preliminary investigations, theoretical modelling and simulation examination of newly proposed methodology. (September 2019) - Jindal, Sumit Kumar; Mahajan, Ankush; Raghuwanshi, Sanjeev Kumar
Pressure is a key unit of measure in aerospace industries. Spontaneous precise measurement of pressure has to be compassed at locations where it is futile and impractical to couple the pressure responsive constituent to the conditional electronics or computational circuit by practicing standard cables and measurements prone to harsh environment. This paper introduces the design of a wireless pressure-monitoring system for aerospace applications in harsh environment. Traditionally, applied pressure deflects a delicate silicon diaphragm, altering the capacitance developed between it and metal electrode firm on a substrate. The LC circuit translates the pressure variation into the LC resonant frequency shift. This change is sensed remotely by virtue of inductance coupling, expelling the compulsion for wire connection rooted telemetry circuits. Novelty of our work rests in the fact that contrary to examining shift in the resonant frequency due to the applied pressure, we have put in effort to maintain resonant shifting equal to zero by varying the capacitance at the observer unit. This will allow pressure variations to be measured directly in terms of the capacitance variation at a fixed resonant frequency, which is 7.92 MHz in our context. According to the application domain (avionics), the proposed sensor structure is designed for functioning in the pressure range between (100 and 1140) mbar. The choice of design values for sensor parameters has been validated. The sensitivity is measured to be 1.746e−17 F/Pa over specified linear range which is shown to match a theoretical estimate realized by mathematical model. An in-depth, step by step derivation of performance parameters to achieve above-stated objective is shown for sensor under study. The results generated are modelled and examined using MATLAB. The analysis conducted dovetail perfectly with the modelled results.